Potential for coastal and offshore aquaculture in Portugal: Insights from physico-chemical and oceanographic conditions - Mosqueira, Miguel (2022)
Physico-chemical and biological parameters along the Portuguese coast were analyzed to evaluate the potential to produce aquatic species of economic interest. Water samples were collected in 2018 and 2019 in five different areas of the Portuguese coast. Currents data were collected between 2018 and 2020 and historical waves height data from 1988 to 2019. According to the results, there is a wide variety of species that can be considered for production. The northernmost area presented the lowest temperature, as well as the highest levels of chlorophyll a, and nitrate. Under such conditions, the rearing of salmon Salmo salar, mussel Mytilus edulis, scallop Pecten maximus, macroalgae Porphyra umbilicalis, and Undaria pinnatifida can be considered. Regarding the southernmost area, due to the highest temperature, this area seems appropriate for the production of meager Argyrosomus regius, sea bream Sparus aurata, sea bass Dicentrarchus labrax, and greater amberjack Seriola dumerili. This study highlights the challenges in deploying aquaculture structures on the Atlantic coast due to its oceanographic conditions. Site selection for aquaculture is a complex process and pilot studies are essential to analyze the feasibility of developing offshore aquaculture along the coast of Portugal.